Polymer and small molecule based hybrid light source - (:unkn) unknown (Osram Opto Semiconductors Gmbh, 2010)
An organic electroluminescent device, includes: a substrate; a hole-injecting electrode (anode) coated over the substrate; a hole injection layer coated over the anode; a hole transporting layer coated over the hole injection layer; a polymer based light emitting layer, coated over the hole transporting layer; a small molecule based light emitting layer, thermally evaporated over the polymer based light emitting layer; and an electron-injecting electrode (cathode) deposited over the electroluminescent polymer layer.
Keywords: Organic electroluminescent device; Organic Phosphor (313/504); Electrode (anode); With Particular Phosphor Or Electrode Material (313/503); Plural Layers (313/506); Electrode (cathode); Fluroescent, Phosphorescent, Or Luminescent Layer (428/690)